Predictors of success in selective laser trabeculoplasty for primary open angle glaucoma in Chinese - Lee JW (Dove Medical Press, 2014)
Jacky WY Lee,1,2 Catherine CL Liu,3 Jonathan CH Chan,4 Raymond LM Wong,5 Ian YH Wong,2 Jimmy SM Lai2 1The Department of Ophthalmology, Caritas Medical Centre, Hong Kong, SAR, People’s Republic of China; 2The Department of Ophthalmology, The University of Hong Kong, Hong Kong, SAR, People’s Republic of China; 3Department of Applied Mathematics, The Hong Kong Polytechnic University, Hong Kong, SAR, People’s Republic of China; 4The Department of Ophthalmology, Queen Mary Hospital, Hong Kong, SAR, People’s Republic of China; 5The Department of Ophthalmology and Visual Sciences, Hong Kong Eye Hospital, Hong Kong, SAR, People’s Republic of China Purpose: To determine the predictors of success for adjuvant selective laser trabeculoplasty (SLT) in Chinese primary open angle glaucoma (POAG) patients. Methods: This prospective study recruited Chinese subjects with unilateral or bilateral POAG currently taking medication to reduce intraocular pressure (IOP). All subjects received a single session of 360° SLT treatment and continued their medications for 1 month. SLT success was defined as IOP reduction ≥20% at 1 month. The following covariates were analyzed in both groups via univariate and multivariate analyses: age, sex, lens status, initial IOPs, post-SLT IOPs, number and type of medications, SLT shots and energy, and pre-SLT investigations.Results: In 51 eyes of 33 POAG subjects, the success rate of SLT was 47.1%. Certain groups of patients were associated with greater success using univariate analysis. These groups included the following: older age (coefficient =0.1; OR: 1.1; P=0.0003), a higher pre-SLT IOP (coefficient =0.3; OR: 1.3; P=0.0005), using four types of antiglaucoma medication (coefficient =2.1; OR: 8.4; P=0.005), a greater degree of spherical equivalent (coefficient =2.1; OR: 8.4; P=0.005), and the use of a topical carbonic anhydrase inhibitor (coefficient =1.7; OR: 6.0; P=0.003). None of the covariates were significant using multivariate analysis. Conclusion: Older age, a higher pretreatment IOP, using multiple antiglaucoma medications especially topical carbonic anhydrase inhibitor, and higher refractive errors were associated with greater SLT success. Keywords: primary open angle glaucoma, selective laser trabeculoplasty, intraocular pressure, success, Chinese